Public goods theory and the provision of refugee protection: The role of the joint-product model in burden-sharing theory - Betts, A (2003)
Much of the existing forced migration literature on burden-sharing implicitly or explicitly assumes humanitarian provision to refugees, whether in the form of asylum or contributions to international refugee agencies, to be an international public good. This assumption has profound implications because it is interpreted to imply that refugee provision is inevitably characterized by collective action failure in the absence of a highly integrated formal regime structure. However, the existing debate has yet to identify explicitly what those public benefits are or to distinguish between the range of benefits and their varying degrees of excludability between states. This paper attempts to address these shortcomings by introducing the notion of 'joint-products' to the burden-sharing debate, arguing that there are multiple benefits, varying in their degree of excludability, that accrue to the providing states. The policy implications for regime structure and the incentives required to induce provision are explored.